Breeding performance, spawning and nursing of black carp (Mylopharyngodon piceus) (Bangladesh Journal of Zoology, 2015)
Successful induced breeding of black carp was performed by using Pituitary Gland (PG) extract and synthetic hormone FlashTM. For PG, the female received two doses at the rate of 2 mg/Kg and 8 mg/Kg body weight respectively; where male received only single dose at the amount of 2 mg/Kg body weight. For Flash, the male and female was received only one dose at the amount of 0.3 ml/Kg body weight for male and 0.25 ml/Kg body weight for female respectively. The ovulation period was 12 hours for PG and 11 hours for Flash after lost injection. In total 6.1 Kg of hatchling was obtained from 23 kg of female black carp under the two treatments. While, the ratio of hatchling and female fish body weight was 1 : 4.28 for PG and 1 : 3.34 for Flash. The study also indicates that the spawn Production of black carp and nursery operation ware profitable. In the spawn production, the profit rate was 872.76% ware observed and the cost benefit ratio recorded as 1: 8.72. In cases of profit from spawn production and nursery operation combined of black carp, the return was 247.95%. While, cost benefit ratio was 1 : 2.47. For income generation through hatchery and nursery operation for sustainable aquaculture extensive study is needed in this regards.Bangladesh J. Zool. 43(1): 73-83, 2015